New Nepticulidae species (Insecta: Lepidoptera) from the Yucatán Peninsula - Stonis, Jonas R.; Remeikis, Andrius; Diškus, Arūnas; Noreika, Remigijus (Zootaxa, 2013)
Thirty-eight species of Nepticulidae are known from the Yucatán Peninsula and adjacent areas (mainland Mexico and Be-lize). This paper describes two new species: Stigmella maya Remeikis & Stonis, sp. nov. (a leaf-miner of Karwinskia hum-boldtiana, Rhamnaceae), and Acalyptris yucatani Remeikis & Stonis, sp. nov. (a leaf-miner of Schinus sp., Anacardiaceae). S. maya is among the smallest Lepidoptera in the world. In its male genitalia S. maya resembles a sizeable group of undescribed species occurring in the Andes (Patagonia: Argentina). The adults of both new species are illustrated with photographs of adults, genitalia and leaf-mines.